Pelatihan seperti apa yang dapat mendukung implementasi kebijakan: perspektif peserta - evaluasi training manajer mid-level untuk imunisasi di Kota Banda Aceh - Alfian R Munthe; Mubasysyir Hasanbasri; Hari Kusnanto (Jurnal Kebijakan Kesehatan Indonesia, 2013)
Background: Training is an effort to develop knowledge andskills and change attitudes through learning experiences toachieve effective perfomance in an activity or range ofactivities. Tsunami disaster on December, 26th 2004 attackedAceh Province, in 2007-2009, the Ministry of Health incollaboration with UNICEF/PATH conducted mid levelmanagement training on immunization in Aceh Province withthe main objective to improve performance of health workerswho served as manager in implementing the policy of nationalprogram on immunization service at the provincial level, district/city and clinic.Research: This is a case study design using descriptivequalitative and quantitative analysis. The unit of analysis is themanagers of the immunization in District Health Office and inthe health centres that have been trained in Banda Aceh. Themethods of data collection are brainstorming, in-depthinterviews, focus group discussions, reports and documents,and assesment.Result: Immunization managers have a good knowledge ofmanagement and type of the vaccine, vaccine logistics, placeand schedule of vaccinations. The number of cases ofdiseases preventable by immunization have decreased andresults coverage of routine immunization has been increasingafter mid-level management training.Conclusion: Trainees have a positive reaction to training,results of immunization coverage and knowledge wereincreased and behavioral change occured.Keywords: Evaluation, Training Mid Level Management,Immunization.